Happiness and domain satisfaction: Theory and evidence - Richard A. Easterlin; Onnicha Sawangfa (Institute for the Study of Labor (IZA), 2007)
In the United States happiness, on average, varies positively with socio-economic status; is fairly constant over time; rises to midlife and then declines; and is lower among younger than older birth cohorts. These four patterns of mean happiness can be predicted rather closely from the mean satisfaction people report with each of four domains – finances, family life, work, and health. Even though the domain satisfaction patterns typically differ from each other and from that for happiness, they come together in a way that explains quite well the overall patterns of happiness. The importance of any given domain depends on the happiness relation under study (by socio-economic status, time, age or birth cohort), and no single domain is invariably the key to happiness.
urn:nbn:de:101:1-20080425105
Keywords: 330; happiness; domain satisfaction; subjective well-being; Lebenszufriedenheit; Sozialer Status; Lebensqualität; USA